A comprehensive review of multi criteria decision making approaches based on interval type-2 fuzzy sets - Celik, Erkan; Gul, Muhammet; Aydin, Nezir; Gumus, Alev Taskin; Guneri, Ali Fuat (Knowledge-based systems, 2015)
•A literature review of IT2FSs based MCDM approaches is presented.•The systematic classification covers 35 MCDM approaches as single and hybrid.•It provides an insight for researchers on IT2FSs based MCDM approaches. Multi criteria decision making (MCDM) is a discipline of operations research which has widely studied by researchers and practitioners. It deals with evaluating and ranking alternatives from the best to the worst under conflicting criteria with respect to decision maker(s) preferences. Since, many real-world systems include uncertainty and vagueness in information, MCDM uses fuzzy sets. In recent years, as an extension of the traditional fuzzy sets concept, type-2 fuzzy sets are preferred to have the capability of handling more uncertainty, and hence, to produce more accurate and robust results, MCDM approaches based on interval type-2 fuzzy sets (IT2FSs) have been published in various subjects. This paper reviews 82 different papers using various MCDM approaches based on IT2FSs which are classified into 35 categories. All papers with respect to single and hybrid approaches are discussed, pointing out their real applications or empirical results and limitations. Furthermore, the papers are statistically analyzed to show new trends within the context of IT2FSs. This systematic and comprehensive review study provides an insight for researchers on interval type-2 fuzzy MCDM in terms of showing current state and potential areas to be focused in the future.